Determination of number of clusters of ECG P-wave morphology estimates by testing hypothesis about uniformity of distribution - Šimoliūnienė, Renata; Kriščiukaitis, Algimantas; Šaferis, Viktoras; Šimatonienė, Violeta (Lietuvos matematikos rinkinys, 2021)
Cardiac output is controlled by the autonomic nervous system by changing the heart rate and/or the contractions of the heart muscle in response to the hemodynamic needs of the whole body. This control is a result of permanent competition between the sympathetic and the parasympathetic nervous systems. Malfunction of these mechanisms causes the postural orthostatic tachycardia syndrome and/or the chronic fatigue syndrome. Evaluation of functionality and efficiency of the control mechanisms can give valuable diagnostic information in the early stages of dysfunction of the heart control systems and help to monitor the healing process or rehabilitation period after interventions. Quantitative evaluation of ECG P-wave changes evoked by an orthostatic test (which evokes a sudden misbalance in the interplay between the sympathetic and the parasympathetic heart control) by using a newly developed method based on the principal component analysis and clusterization by testing statistical hypothesis of uniformity provides a quantitative estimate for functionality and efficiency of the heart rate control mechanisms.
Keywords: Eng; sympathetic and parasympathetic nervous systems; ECG P-wave morphology; principal component analysis; clusterization by testing statistical hypothesis of uniformity